Correlations between anthropometric characteristics, heart rate and the results of the 8-second skipping with hand clapping (SHC) test in preschool children - Podstawski, Robert; Konopka, Stanisław; Mańkowski, Stefan; Choszcz, Dariusz; Borysławski, Krzysztof (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Anthropometric measurements and the BMI are taken into account in the process of developing physical fitness tests for children. Aim of Study. The aim of this study was to describe the relationships between the anthropometric characteristics (body mass, body height, length of lower and upper limbs), BMI and speed abilities of preschool boys and girls performing the 8-second skipping with hand clapping (8-s SHC)test. The increase in HR during the test was also determined. Material and Methods. The test involved 60 girls and 57 boys aged 68.2 ± 11.33 months (min. – 56, max – 89). Their body mass, body height, length of lower and upper limbs and BMI were determined, and their speed abilities were evaluated with a 8-sSHC test. The participants’ HR was measured before and after the test, and the exercise-induced increase in HR was calculated. The basic statistics were determined for all evaluated parameters and the coefficients of correlation between anthropometric features, HR, and the number of claps during the test were calculated. Results. Among the analyzed parameters, only body mass and BMI were significantly higher in boys than in girls. Mean HR increased during the 8-s SHC test in both girls and boys (to 149.40 and 152.9 bpm, respectively). The number of claps during the 8-s SK test increased significantly with an increase in the values of anthropometric measurements. Significant correlations between the analyzed parameters were not determined only for BMI and heart rate after the 8-s SK test. Conclusions. Anthropometric characteristics such as body mass, body height, length of lower and upper limbs significantly influenced the speed abilities of kindergarteners performing the8-s SK test, whereas BMI was not significantly correlated with the results of the test
Keywords: anthropometric characteristics; BMI; motor test; speed abilities; skipping with hand clapping for 8-s; changes in HR